Characteristics of liquid upwash formed on a splash plate. (February 2018) - Inamura, Takao; Endo, Sosuke; Okabe, Takahiro; Fumoto, Koji
Highlights: The characteristics of an upwash was theoretically analyzed. The experiments were conducted to measure the upwash thickness and velocity. The calculations of an upwash thickness and velocity were compared with experiments. The vortices in an upwash base influence on an upwash formation. Abstract: The present study attempts to clarify the characteristics, i.e., the sheet thickness and sheet velocity, of a liquid upwash formed by the oblique impingement of two equal liquid jets on a splash plate. Moreover, the results are compared with those obtained by the theoretical analysis derived in the previous paper. First, the equations of sheet thickness and sheet velocity of the upwash were derived using the theoretical analysis developed in the previous paper. Second, the upwash thickness and velocity were measured by the electric resistance method and the PIV method, respectively. Finally, the predictions of the upwash thickness and velocity obtained by the theoretical analysis were compared to the measurement results, and the validity of the theoretical analysis was verified.